Company Policy Model on Products and Services in the Implementation of After Sales Services in Indonesia - Teruna, Dipa; Ardiansyah, Tedy (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
After-sales service is a key part of maintaining and increasing customers for companies, both for products and services, but the problem is that it is very complicated to maintain, let alone increase customers. The problems that arise are classic problems in the form of company illnesses in the form of service quality, product non-conformities, stock and delivery, employee training, IT systems and technology, and internal coordination for changes in technology and products. The aim of this research is to find out from the informants what the most dominant key words are that are often mentioned by the informants and how to compare gender and type of company in producing the most dominant variables for after-sales service. This is qualitative research with a phenomenological approach. Phenomenologists describe the main points of each informant's life experiences. Phenomenologists describe in detail from informants where the informants feel a phenomenon. The sample determined that five informants had expertise in their fields, as proven by their top positions in their companies. The analysis of this research was assisted by qualitative tools from Nvivo 12, and there is no doubt about international evidence, especially in data testing or analysis tests. The research instrument was adopted from previous research and assisted by theoretical studies to simplify and help determine policies for the company's after-sales service. The results obtained were that five informants had strong and moderate relationship values for each informant included. The comparison diagram or chart test is unique in that each informant, whether gender, female, or male, shows that the customer service variable has the strongest relationship with after-sales service.